2023
DOI: 10.1038/s41467-023-39435-z
|View full text |Cite
|
Sign up to set email alerts
|

A PPP-type pseudophosphatase is required for the maintenance of basal complex integrity in Plasmodium falciparum

Abstract: During its asexual blood stage, P. falciparum replicates via schizogony, wherein dozens of daughter cells are formed within a single parent. The basal complex, a contractile ring that separates daughter cells, is critical for schizogony. In this study, we identify a Plasmodium basal complex protein essential for basal complex maintenance. Using multiple microscopy techniques, we demonstrate that PfPPP8 is required for uniform basal complex expansion and maintenance of its integrity. We characterize PfPPP8 as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…Another obvious advantage of U‐ExM is that it is compatible with most super‐resolution imaging modalities, increasing the potential usefulness of the technique. To date, Airyscan (Calla et al, 2023; Liffner & Absalon, 2021; Liffner et al, 2023; Morano et al, 2023) is the only super‐resolution technique that has been used on expanded parasites to the best of our knowledge, but stimulated emission depletion (STED) (Gambarotto et al, 2019), 3D structured illumination microscopy (SIM) (Woglar et al, 2022) and single molecule localization microscopy (SMLM) (Chang et al, 2023) have been applied to U‐ExM on other sample types. Additionally, U‐ExM may increase antibody accessibility for certain proteins, with reduced antibody competition having been previously observed for expanded microtubules (Gambarotto et al, 2019).…”
Section: Advantages Drawbacks and Limitations Of U‐exm In Apicomplexamentioning
confidence: 99%
“…Another obvious advantage of U‐ExM is that it is compatible with most super‐resolution imaging modalities, increasing the potential usefulness of the technique. To date, Airyscan (Calla et al, 2023; Liffner & Absalon, 2021; Liffner et al, 2023; Morano et al, 2023) is the only super‐resolution technique that has been used on expanded parasites to the best of our knowledge, but stimulated emission depletion (STED) (Gambarotto et al, 2019), 3D structured illumination microscopy (SIM) (Woglar et al, 2022) and single molecule localization microscopy (SMLM) (Chang et al, 2023) have been applied to U‐ExM on other sample types. Additionally, U‐ExM may increase antibody accessibility for certain proteins, with reduced antibody competition having been previously observed for expanded microtubules (Gambarotto et al, 2019).…”
Section: Advantages Drawbacks and Limitations Of U‐exm In Apicomplexamentioning
confidence: 99%
“…Of the three dynamin-related proteins in P. falciparum, PfDyn1 is thought to play a role in hemoglobin uptake 43,68 , PfDyn2 is required for apicoplast and mitochondrial division (this study), and PfDyn3 remains unknown. Immunoprecipitation of basal complex proteins 69 detected the presence of PfDyn2, indicating PfDyn2 could be involved in basal complex contraction or performing the final scission of merozoites in lieu of ESCRT-III machinery [70][71][72] , which apicomplexan parasites lack. However, in some PfDyn2-deficient parasites, we observed that amitochondrial merozoites which separate from the schizont have fully contracted basal complexes (Figure 4a), suggesting that PfDyn2 is not directly involved in basal complex contraction.…”
Section: Discussionmentioning
confidence: 99%
“…5, Live cell imaging. The long-term live cell imaging experiments were carried out as previously described 69 . Some minor modifications are shown in Supplementary Experimental Procedures.…”
Section: Star Methodsmentioning
confidence: 99%
“…For example, biogenesis of apical organelles including the rhoptries and micronemes occurs de novo . The IMC, a double layered membranous structure located beneath the plasma membrane (PM) [ 16 ] is pulled around the newly-forming daughter cells by the basal complex (BC), whose integrity is maintained by the PPP-type pseudophosphatase PPP8 [ 34 ] and acts as a contractile ring to constrain and define daughter cell boundaries [ 35 ]. Several proteins are known to be essential for IMC and BC biogenesis, including IMC sub-compartment proteins (ISP)1 and 3, merozoite organising protein and CINCH [ 36–38 ], and others [ 39 ].…”
Section: Introductionmentioning
confidence: 99%